(untitled) (Web of Teachers: Inderscience Research, 2025)
In today’s world of globalization, the development of critical thinking is manifested as one of the most important components of human life. In the conditions of rapid development of information technologies, digital transformation processes and socio-economic transformations, the ability of a person to make independent, logical and informed decisions is of great importance. The article analyzes the content of critical thinking, its role in the educational process and its role in the professional development of young people. At the same time, the main mechanisms and effective methods of developing critical thinking are discussed. The results of the presentation show that the formation of critical thinking competencies has a significant positive impact on the development of society.